The Effect of Organizational Commitment and Perceptions of Organizational Support (POS) on Turnover Intention at PT Aman World Logistics - Silviya Rachmawati; Bayu Airlangga Putra; Ani Wulandari; Qausya Faviandani (Jurnal Ekonomi, 2021)
The problem of this research is about organizational commitment and Organizational Support Perception is partial and together (simultaneously) a significant effect on turnover intention in PT Secure World Logistics. The population of the research is all sixty-three employees of PT Aman World Logistics, with a saturated sample technique. The sample in this research took all sixty-three employees of PT Aman World Logistics. The method of this research is multiple linear regression analysis. Based on the results of the analysis and discussion, it can be concluded that the variable organizational commitment (X1) and perceived organizational support (X2) partially and together (simultaneously) have a significant effect on turnover intention (Y).